Creating a culture of philanthropy. Issue 2 (8th August 2016) - Whitchurch, Jesse; Comer, Alberta
Abstract : Purpose: With the retirement of the External Relations Director in early 2014, the Marriott Library's new Dean used this opportunity to move library fundraising in a new direction. This paper aims to examine one approach to institutionalizing philanthropy to increase its effectiveness and creates a plan for implementation. Design/methodology/approach: Changing the position expectations and hiring a new Development Director to lead the change has proven beneficial to the library staff and donors. The new Development Director and Dean are changing the culture of development at the Marriott Library by not only working closely with library faculty and staff but also through making them partners in all aspects of development work. Findings: Although the new program has only been in place for a little more than a year, positive outcomes are already emerging. These include a more engaged staff, better served donors and an increase in donations to the library including, a multi-million dollar gift for a major renovation as well as a US3.5 m gift of rare materials. Originality/value: While there has been a lot of research on development, little of it focuses specifically on the assets and challenges libraries face within the context of large universities. This paper discusses the advantages and disadvantages of library fundraising and offers a model of how libraries can leverage their staff and central role within the university.